Lutter contre l’« esclavage numérique » en marge des syndicats - Fabien Brugière; Jean Vandewattyne (Sociologies)
Based on an ethnographic survey of two Brussels-based delivery worker collectives, this article examines union struggles in the platform economy through the prism of the moral dimension. The first step is to analyze the dynamics of collective action, demonstrating the role played by the moral economy of the professional group as a mobilizing factor in the face of worsening employment conditions. Secondly, the militant activity and structure of the collectives can be interpreted as the product of moral crusades, oscillating between opposition to trade unions and convergence with institutional moral entrepreneurs.